Inclusion of students with specific educational needs: a structured path for changes (Olhar de Professor, 2020)
Inclusion in the educational environment is a continuous challenge in many educational institutionsand is characterized by multiple actors, bias, conflicts and lack of clear information. Although the operationalguidelines for Specialized Educational Assistance are required by law, the practical implementation of suchguidelines depends on contextual immersion where it is applied. The purpose of this paper is to identify activitiesnecessary for the inclusion of students with Specific Educational Needs through an approach involving Problem-Structuring Methods. For this purpose, a multi-methodology was assembled that combines the classical approachesof Value-Focused Thinking and Soft System Methodology. The constructed multi-methodology was applied in acase study in a unit of the Federal Education System. The main results indicate that some established assumptionsshould be re-evaluated in the light of the present study.
Keywords: Specialized Educational Service. Special Education. Operational Research. Problem Structuring Methods.